O-10 Collaborative multidisciplinary clinics increase access to patients with non-malignant disease. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Wilderspin, Nicola; Gijselhart, Claire; Jubb, Gill; Westwood, Debbie; Challand, Simon
Abstract : Background: Few patients with non-malignant disease access hospice care despite having similar care and support needs to cancer patients. Aims: To increase access to hospice care and advance care planning for patients with non-malignant diseases, and to enable choice in end of life care and improved carer support. Methods: Separate hospice-based multi-disciplinary clinics were established for patients with advanced heart failure; respiratory and Parkinson's disease; and end-stage renal failure. The four clinics are staffed by a disease-specific physician, a palliative medicine physician, a hospice-based multidisciplinary staff and volunteer team and NHS-based disease specific clinical nurse specialists. Clinical assessments focus on quality of life, advance care planning and carer support, making onward referrals to other services as required. We report four years' experience of this new model of care. Results: Between April 2013 and March 2017, a total of 435 patients attended the clinics, with 1036 attendances. Patients with heart failure were the largest group (30%); with 29% being respiratory patients; 23% Parkinson's disease and 18% renal failure. 318 patients (73%) engaged in advance care planning discussions, with 66 patients completing formal advance statements and 28 completing advance decisions to refuse treatment. 289 (66%) patients have made decisions to refuse cardiopulmonary resuscitation. 67 (15%) of patients had died by the end of March 2017, of whom 52 (78%) were supported to enable death in community settings (home 39%; hospice 22%; care homes 13%; other 9%). Only 12 patients (18%) died in hospital. Clinic patients and carers report improved quality of life and accessed multiple hospice and community based services as a result of initial clinic review. Conclusions: Collaboration between hospice, acute hospital and community trust health professionals has enabled mutual support and learning and provided a popular care model for patients with non-malignant diseases.